2015
DOI: 10.1097/ccm.0000000000001090
|View full text |Cite
|
Sign up to set email alerts
|

Talactoferrin in Severe Sepsis

Abstract: Administration of oral talactoferrin was not associated with reduced 28-day mortality in patients with severe sepsis and may even be harmful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…A single multicenter trial was conducted using talactoferrin in 750–1500 g neonates, which examined 120 infants and showed a trend towards decreased infectious morbidity but did not achieve statistical significance [ 125 ] ( Table 1 ). Further trials with this protein, however, currently appear to be on hold following recent data showing no benefit in a trial in adult ICU patients [ 126 ].…”
Section: Examination For Clinical Efficacy Of Lf In Neonatesmentioning
confidence: 99%
“…A single multicenter trial was conducted using talactoferrin in 750–1500 g neonates, which examined 120 infants and showed a trend towards decreased infectious morbidity but did not achieve statistical significance [ 125 ] ( Table 1 ). Further trials with this protein, however, currently appear to be on hold following recent data showing no benefit in a trial in adult ICU patients [ 126 ].…”
Section: Examination For Clinical Efficacy Of Lf In Neonatesmentioning
confidence: 99%
“…A second trial utilized similar enrollment criteria and treatment in randomizing 205 patients. The 28-day all-cause mortality in the hLF arm was 25 % compared to 18 % in the placebo group ( p = 0.11), although ICU and long-term mortality were increased in the hLF group [ 45 ]. However, on combining the results of the two trials in a meta-analysis, the relative risk of hospital mortality was 0.88 (95 % CI 0.35 to 2.26) (unpublished data).The cause for the discrepant results between these studies is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Due to conflicting results on the effects of LF when used as a treatment for sepsis [ 44 , 45 ] a priori, we will conduct a subgroup analysis of patients presenting with sepsis [ 46 ]. No formal interim analyses are planned.…”
Section: Methodsmentioning
confidence: 99%
“…APPs have potential as stand alone therapeutics or as adjunctive agents, to reduce either length of antibiotic treatment and/or inflammation induced by killed microbes/microbial products ( 52 ). Important APPs that have undergone clinical trials include rBPI 21 ; Pexiganan, an analog of Magainin (MSI-78) ( 53 ); Iseganan (IB-367), a protegrin mimetic; Omiganan pentahydrochloride (CLS001), an Indolicidin analog; Brilacidin, a defensin mimetic; LTX-109, a short lactoferricin-based peptide ( 54 ), and Talactoferrin, an analog of LF ( 55 , 56 ). The terms analog and mimetic are used, respectively, to describe synthetic compounds with closely similar molecular structure versus those with a closely similar functional capacity to that of an endogenous APP (see Table 4 ).…”
Section: What Are Antimicrobial Peptides and Proteins?mentioning
confidence: 99%
“…Several pharmaceutical companies are developing APPs for systemic administration, such as Agennix AG who are pursuing the development of oral Talactoferrin in severe sepsis (NCT00630656). Results from their phase II randomized controlled trial (RCT) showed a significant reduction in all-cause mortality at 28 days and 6 months in the treatment group ( 82 ) yet, the recent follow on phase II/III RCT (OASIS trial) was terminated prematurely over concerns of safety and efficacy ( 55 ). Interestingly the APP that has undergone most advanced clinical testing using the intravenous (IV) route is rBPI 21 , which was assessed for its efficacy in meningococcemia in children ( 42 ).…”
Section: Clinical Application Of Apps: Promising Evidence From Clinicmentioning
confidence: 99%